REKRUTMEN TENAGA KERJA HOUSEKEEPING DI GRAND JATRA HOTEL PEKANBARU - Kartini "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In the recruitment process of Housekeeping department at Grand Jatra Hotel Pekanbaru is prefer to the age and experience without think about the background of education, so the recruitment of the employees have quality in terms of its skill of housekeeping. Because Grand Jatra Hotel Pekanbaru is a 5-star hotel which is employees especially in the housekeeping department must has skill in the make up room, also another skill in Tata Graha, that skill is needed to has profesional and competence housekeeping employees with other hotels in Pekanbaru.The purpose of this research was to analyze recruitment process of Housekeeping department at Grand Jatra Hotel Pekanbaru. The research’s design used is descriptive qualitative method approach, this research to describe the real phenomenon. The indicators that want to present and and analyze by interval size as the type of measurement, while the formula used is the Likert Scale i = . The indicators of houskeeping recruitment at Grand Jatra Hotel Pekanbaru is the basic of recruitment, the recruitment’s sources, recruitment’s method, and recruitment’s constraints.Grand Jatra Hotel Pekanbaru itself has already implemented most of the criteria for indicators that have been specified, based on the respondents results’ recapitulation said "Strongly agree", with the recruitment process conducted by the Human Resources Department and based on the participannts who has responsiblity for the recruitment process. The total score was 11.43 which lies between 4.3 to 5 are "Strongly Agree" category.Key words: Recruitment, Housekeeping, Grand Jatra Hotel Pekanbaru